Colonoscopy: Advanced and Emerging Techniques—A Review of Colonoscopic Approaches to Colorectal Conditions - Kumar, Anjali S.; Lee, Jennifer Kim (Clinics in Colon and Rectal Surgery, 2017)
A complete colonoscopy is key in the diagnostic and therapeutic approaches to a variety of colorectal diseases. Major challenges are incomplete polyp removal and missed polyps, particularly in the setting of a difficult colonoscopy. There are a variety of both well-established and newer techniques that have been developed to optimize polyp detection, perform complete polypectomy, and endoscopically treat various complications and conditions such as strictures and perforations. The objective of this article is to familiarize the colorectal surgeon with techniques utilized by advanced endoscopists.
Keywords: colonoscopy; endoscopic submucosal dissection; chromoendography; colonic stents